SEA WATER AREAS OF THE URALIAN REGION IN THE MIDDLE AND LATE CRETACEOUS - Amon E.O. (My University, 2001)
Middle and Late Cretaceous paleogeography of the Great Urals is considered. Emphasis is placed on the sea basins existing in region. A nomenclature of basins is proposed. The temporal variations in their outlines and areas are traced. The positions of straits and the directions of biota migration are outlined.
Keywords: Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая